Високотемпературні сенсори деформації на основі ниткоподібних кристалів фосфіду галію - Дружинін, А.О.; Мар’ямова, І.Й.; Кутраков, О.П. (Технология и конструирование в электронной аппаратуре, 2019)
Проведено дослідження тензометричних характеристик ниткоподібних кристалів фосфіду галію р-типу провідності, легованих цинком. На основі цих кристалів створено сенсори деформації, працездатні в інтервалі деформацій ±1,2·10⁻³ відн. од. і широкому діапазоні температур — від 20 до 550°С. Проведено исследование тензометрических характеристик нитевидных кристаллов фосфида галлия р-типа проводимости, легированных цинком. Па основе этих кристаллов созданы сенсоры деформации, работоспособные в интервале деформаций ±1,2-10⁻³ опт. ед. и широком диапазоне температур от 20 до 550°С. The paper presents a study of tensoresistive characteristics of p-type GaP whiskers with [111] crystallographic orientation coinciding with the direction of the maximal piezoresistive effect for this material. The authors present a newly-developed technology of creating the ohmic contacts to GaP crystals that allows using these crystals at high temperatures (400—600°C). Tensoresistive characteristics of p-type GaP whiskers were studied in the strain range of ±1,2·10⁻³ rel. un. These studies show that the gauge factor for these crystals at 20°C is rather large. Thus, for p-type GaP crystals with a resistivity of 0.025—0.03 Ω·cm, the gage factor is in the range of 90—95.